Bracoviruses recruit host integrases for their integration into caterpillar's genome. - Zehua Wang (Public Library of Science (PLoS), 2021)
Some DNA viruses infect host animals usually by integrating their DNAs into the host genome. However, the mechanisms for integration remain largely unknown. Here, we find that Cotesia vestalis bracovirus (CvBV), a polydnavirus of the parasitic wasp C. vestalis (Haliday), integrates its DNA circles into host Plutella xylostella (L.) genome by two distinct strategies, conservatively and randomly, through high-throughput sequencing analysis. We confirmed that the conservatively integrating circles contain an essential "8+5" nucleotides motif which is required for integration. Then we find CvBV circles are integrated into the caterpillar's genome in three temporal patterns, the early, mid and late stage-integration. We further identify that three CvBV-encoded integrases are responsible for some, but not all of the virus circle integrations, indeed they mainly participate in the processes of early stage-integration. Strikingly, we find two P. xylostella retroviral integrases (PxIN1 and PxIN2) are highly induced upon wasp parasitism, and PxIN1 is crucial for integration of some other early-integrated CvBV circles, such as CvBV_04, CvBV_12 and CvBV_24, while PxIN2 is important for integration of a late-integrated CvBV circle, CvBV_21. Our data uncover a novel mechanism in which CvBV integrates into the infected host genome, not only by utilizing its own integrases, but also by recruiting host enzymes. These findings will strongly deepen our understanding of how bracoviruses regulate and integrate into their hosts.